Platelet Hyper-Aggregation and Abnormalities of Coagulation Factors in Young Diabetic Patients (Medicine Today, 2014)
Diabetic vascular disease is conveniently divided into two main categories: microvascular diseases and macrovascular diseases. The changes involving the smallest blood vessels - the capillary and pre-capillary arteriolesare microvascular changes. The cross sectional case-control study was done on forty young diabetic patients for their platelet aggregation response to ADP, plasma fibrinogen and vWF in relation to the age and BMI matched 10 nondiabetic control subjects (Age in years : 23.7 ± 2.26 in control vs 24.33 ± 3.29 in subjects, and BMI in kg/m2. The lipid profile, C-peptide, C-peptide: glucose and other anthropometric measurements of the diabetic and control subjects were also measured to find out any possible correlation. The platelet aggregation with ADP in diabetics was found to be significantly higher (in diabetics 76.56 ± 16.92 percent compared to controls 62.90 ± 12.35 percents; (P< 0.27). Plasma fibrinogen and plasma von Willebrand factors were found to be significantly higher in young diabetics compared to the non-diabetic counterparts (Plasma fibrinogen in mg/l; 1075.90 ± 455.16 in control vs 1569.15 ± 731.42 in diabetic, P